A Project Study on the product, Scented Oil with Insect Repellant - Caoyonan, Lizelle Anne T.; De Leon, Irene R.; Musngi, Cherrie Vi C. (Diliman, Quezon City College of Engineering, 2000)
The Scents Plus! Scented Oil with Insect Repellant is a newly patented product conceptualized by Dr. Antonio F. Mateo. It is a tangible non-durable product that is basically an air-freshener, with the value-adding features of simultaneously being a room/space deodorizer with insect repellant. The product's formula is composed of proportions of scented oil, mineral oil, and insect repellant chemical. The primary objective in the invention of the product is to provide a reasonably priced non-toxic fragrance with insect repellant, in order that consumers of all ages can enjoy fragrant personal or public spaces while eliminating odor problems and repelling disease-carrying or pestering insects. As a new product, it is to be launched as an entrant in the market for air-fresheners, with its multi-functional quality and low price as its edge against its competitors. Elaborating on the market analysis, the product's target market in the Philippines is composed of households from the upper class to the lower middle class income brackets. The market study shows that the expected market share for the first year of operation is 2.92%. From this, sales plan for the first year is slated at 16,401.61 kg of the product. To target this figure, the marketing budget for the first year is P618,832.00. This value covers sales advertising/promotions, product launching, and public relations. The technical study gives an estimate of the Total Project Cost, which amounts to P25,475,663.57. This cost provides a 10% allotment for contingency cost. The technical study presents recommendations based on capacity planning, production planning and facilities planning. Based on the alternatives compared and evaluated, it is planned that production be manual, initially with a production force of 48 workers. A suggested plant site is given in the analysis, together with the suggested plant layout. From the financial analysis, it can be seen that the business should be formed as a corporation. P10,000,000 is to be loaned and additional funds are to be gathered from the shares of stock offered at P20.00 par value. In the company organization, 61 employees are needed. The organizational study shows the complete organizational structure and the monthly and annual salaries for each employee. The social profitability analysis shows that the business will provide benefits to society such as additional funds for the government, consumer savings, and job opportunities. All in all - in the Market, Technical, Financial, Organizational, and Social Profitability analyses - it can be seen that production of the scented oil with insect repellant product is feasible.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Insect baits and repellents; Participatory monitoring and evaluation (Project management)